Three cases of hypopituitarism with variable presentation - Hossain, Moumita; Ahasanul, Haque; Afrozrafiya,; Bin, Bashar Fuad; Abdur, Rahim; Rafiqul, Islam Mohammad (Bangladesh Journal of Medicine, 2024)
Patients with hypopituitarism often experience a delay in diagnosis. Symptoms which maybe life threatening are nonspecific and often attributed to aging and/or related morbidities. We have diagnosed three patients with hypopituitarism. We treated them accordingly and they dramatically improved. Our first case 60 years old female came to us with sudden onset of vomiting for several times and generalized weakness. She is known case of diabetes mellitus, hypertension and IHD with HF (EF 40%). In routine investigation we found unusual hyponatremia and hyperkalemia. We did pituitary function test as well as other necessary investigation. We found hypopituitarism and pituitary microadenoma in MRI of brain with pituitary protocol.Our second case 43years old female presented to us with vomiting for four months for several times with features of anemia. We did routine investigation and found hypomagnesemia, hypocalcemia, hypokalemia and hypernatremia. In search of previous document, we found hyponatremia, hypokalemia and hypochloremia. For these she admitted into tertiary care hospital and treated as acute gastroenteritis. We did pituitary function along with other possibilities. We found hypopituitarism with multiple endocrine neoplasia. Imaging showed pituitary microadenoma involving left half of anterior pituitary.Our third case 68 years elderly female known to have hypertension and diabetes mellitus came to us with features of meningo-encephalitis. We searched for features of meningo-encephalitis in MRI of brain. We found empty Sella. Pituitary function tests revealed hypopituitarism. Lactational failure and pre mature amenorrhea was absent in all three cases. So, suspicion about hypopituitarism should be kept in mind though clear-cut features are absent to save lives of our patients. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation:178